2010
DOI: 10.1002/ange.201001145
|View full text |Cite
|
Sign up to set email alerts
|

Layered Zinc Phosphates with Photoluminescence and Photochromism: Chemistry in Deep Eutectic Solvents

Abstract: A metal‐activator‐free orange phosphor was synthesized from ZnO/H3PO3/diamine in choline chloride/oxalic acid deep eutectic solvent, which also acted as methylating agent and source of ethylene glycol (EG) by dissociation of choline ions. Interlayer incorporation of a dimethylated amine made the resulting layered zinc phosphate (“ZnPO”, see picture) photochromic, and their interaction with EG formed fluorophores with orange photoluminescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Electron transfer has been found to be one of the subsequent photophysical processes in some reported X-rayinduced photochromic species. [3,4,[7][8][9][10] In this case, electron spin resonance (ESR) studies were carried out to make sure the presence of electron trans- fer during X-ray irradiation. The experimental results showed that compound 1-Y and its decolored samples are ESR silent but 1-HX-B and 1-SX-B display single line signals with g factors of 2.0029 and 1.9988, respectively ( Figure 5).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Electron transfer has been found to be one of the subsequent photophysical processes in some reported X-rayinduced photochromic species. [3,4,[7][8][9][10] In this case, electron spin resonance (ESR) studies were carried out to make sure the presence of electron trans- fer during X-ray irradiation. The experimental results showed that compound 1-Y and its decolored samples are ESR silent but 1-HX-B and 1-SX-B display single line signals with g factors of 2.0029 and 1.9988, respectively ( Figure 5).…”
Section: Methodsmentioning
confidence: 99%
“…Types of electron transfer in known X-ray-induced photochromic species are ligand-to-metal charge transfer, [7, 9b] metal-to-metal charge transfer, [3] metal-centered transitions, [4] charge transfer between inorganic frameworks and organic templates, [8] and charge transfer between inorganic frameworks and doped metals. [10] In our case, the Br!L electron transfer is a key factor for the X-ray-induced photochromism of 1-Y.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first example of two types of zeolite frameworks nested in the same material, and it also demonstrates a new mechanism for the formation of nested cage structure that is distinctly different from the previously reported mechanism based on polyfunctional ligands. [14][15][16] This new type of intercage linking mechanism through metal sites might be adapted for the synthesis of discrete coordination polyhedra as well, which may lead to the creation of sophisticated coordination assemblies, and perhaps a better understanding of selfassembly processes in both synthetic and natural systems. Received: May 3, 2012 Revised: June 5, 2012 Published online: July 12, 2012 .…”
Section: Methodsmentioning
confidence: 99%